Topiramate and Metabolic Acidosis in Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The acid-base metabolism was investigated in 9 infants and toddlers, aged 5 months to 2.3 years (median, 6 months), treated with topiramate (TPM) for seizures at Johannes Gutenberg University, Mainz, Germany.